PENGGUNAAN BAHASA SLANG DI LINGKUNGAN KAMPUS UNIVERSITAS PGRI PALEMBANG - Agus Heru; Siti Rukiyah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The problem in this study was how to use slang in the campus environment at the University of PGRI Palembang, the purpose of this study was to describe the use of slang in the campus environment at the University of PGRI Palembang. The method used in this research is descriptive method. The data source of this research is the students of the Faculty of Engineering Semester II, University of PGRI Palembang. The data collection technique used in this study is the skillful listening technique and note taking technique. The data analysis technique used in this study is the intralingual equivalent technique. Based on the results of the research and discussion, it can be concluded that in the use of slang language for students of the Faculty of Engineering Semester II at the University of PGRI Palembang there were 26 slang words used by the students in their conversation. The use of slang is more dominantly carried out in order to create a relaxed atmosphere and a familiar impression in their association.